A Study on Security issues in Wireless Sensor Networks - Ranjitha, S; Prabakar, D; Karthik, S (International Journal of Computer Sciences and Engineering, 2025)
Wireless Sensor Network (WSN) is a technology that shows great promise for various futuristic applications both for public and private sectors. Its shows by few applications like disaster management system, battlefield environment and etc. In this connection many issues are considered among that Security is the main issue in the WSN. Unauthorized access in an entire networks leads to dilute the security. For providing security to this network between the nodes, we need some specialized algorithms. Previously many more algorithms are used to provide either data security or network security. Cryptographic strategies and Secure Algorithms are the key factor to ensuring that either data transmission or data handling between nodes are occurred securely. Id (Identity) Based Cryptography and Public Key Cryptography are the types of cryptography which are used to provide security to the data based on sharing keys between sender and receiver in the network.